ISOLASI DAN ELUSIDASI STRUKTUR SENYAWA TRITERPENOID DARI KULIT BATANG AMBACANG (Mangifera foetida L.) SERTA UJI BRINE SHRIMP LETALITY TEST (BSLT) - Adlis Santoni; Sabariah -; Mai Efdi (Universitas Andalas, 2015)
A brine shrimp toxic compound has been isolated from Mangifera foetida L. steam bark. Based on spectroscopic data (IR,1H- NMR, 13C-NMR 1D and 2D), the structure of this compound was identified as mangiferenes B, C30H47O2. In this study, the n-hexane, ethyl acetate, methanol extracts and isolated compound showed toxic effects (LC50 471.9543; 534.5209, 678.4421, and 22.1615 Î¼g/mL, respectively). The toxicity degree among the three extracts and isolated compound is isolated compound > n-hexane extract > ethyl acetate extract > methanol extract.